Evaluasi Kesesuaian Standar Pelayanan Minimum (SPM) Terminal Penumpang di Kalimantan Selatan - Jihan Alya Nabillah; Hafsha Yanti Siregar (Yayasan Literasi Sains Indonesia, 2026)
This study aims to evaluate the level of compliance with the Minimum Service Standards (SPM) at Gambut Barakat Terminal, Km 6 Banjarmasin Terminal, and H. Soemarsono Tanah Laut Terminal based on the Regulation of the Minister of Transportation Number 40 of 2015 concerning Minimum Service Standards for Passenger Terminals. This research employed a descriptive evaluative method by assessing the conformity level of facilities and services at each terminal. Data were collected through field observations and documentation based on SPM indicators, including safety, security, reliability or regularity, comfort, accessibility, and equality aspects. The assessment was conducted using a scoring system to determine the level of service fulfillment at each terminal. The results indicate that the implementation of SPM at the three terminals is still uneven. Km 6 Banjarmasin Terminal showed a higher level of service fulfillment compared to the other terminals, while H. Soemarsono Tanah Laut Terminal had the lowest fulfillment level, particularly in safety and equality aspects. The correlation test results revealed a strong positive relationship between terminal classification and the level of SPM fulfillment, indicating that terminals with higher classifications tend to provide more complete facilities and better services. The low level of SPM fulfillment at several terminals is influenced by limited facilities, operational management, and the suboptimal implementation of service standards. The findings of this study are expected to serve as evaluation material for improving the quality of passenger terminal services in South Kalimantan.